Perkembangan Sastra Arab pada Masa Bani Umayyah - Mukammiluddin Mukammiluddin (Jurnal Adabiyah: Humanities and Islamic Studies, 2011)
The progress of Arabic literature in Umayyah Dynasty period increased more than previous time. It is due to some poets had good creativity to make their poems which were inspired by political atmosphere. The rulers also had good appreciation to the poets who skillfully composed their poems. Some awards were given to those who were able to compose such creativity. Therefore, some composers were motivated to more creatively write some song or lyrics which highlighted the Kings.